ASSESSMENT OF KNOWLEDGE, ATTITUDE AND PRACTICE ON TREATMENT PLANNING FOR ESTHETIC CASES BETWEEN SPECIALISTS AND GENERAL PRACTITIONERS - Sneha Pai; Subash Sharma (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
With the development of technology, esthetic dentistry these days has reached new heights. This has led more patients to seek dental treatment to improve esthetics. There are several aspects to be considered while planning esthetic dental treatment which requires a thorough clinical examination and diagnosis. The factors that govern the outcome of esthetic dental treatment comprise both extra oral and intraoral features. These factors aid in the treatment planning which in turn helps predicting the outcome and success of esthetic restorative treatment. This survey aims to assess the knowledge, attitude and practice on treatment planning in esthetic dentistry by specialists and dental practitioners. This survey was carried out by designing a questionnaire containing 15 questions on Google forms which was circulated among dentists. The questions were based on knowledge, attitude and practice on esthetic treatment planning in dentistry. The responses were viewed in M.S. office excel and the results were interpreted using graphs by SPSS 23.0 version. Of the 120 dentists among whom the questionnaire was circulated, 87 responded, showing a response rate of 63.8%. Analysis showed that the dentists showed some lack of theoretical knowledge due to which application of concepts to clinical scenarios was moderate. This survey indicated the need for educational intervention to improve the knowledge, attitude and practice on treatment planning for esthetic cases.